Weak Wardowski contractive multivalued mappings and solvability of generalized phi-Caputo fractional snap boundary inclusions - Jafari, Hossein; Mohammadi, Babak; Parvaneh, Vahid; Mursaleen, Mohammad (Nonlinear Analysis: Modelling and Control, 2023)
In this paper, we introduce the notion of weak Wardowski contractive multivalued mappings and investigate the solvability of generalized '-Caputo snap boundary fractional differential inclusions. Our results utilize some existing results regarding snap boundary fractional differential inclusions. An example is given to illustrate the applicability of our main results.
Keywords: weak Wardowski contractions; multivalued mapping; contractive mapping; phi-Caputo integral; fractional derivative; snap boundary inclusions